The content of riboflavin and its coenzymes forms in the brain of rats of different ages - Fedorko, N. L.; Petrov, S. S.; Nikolaienko, K. V. (Journal of Education, Health and Sport, 2017)
The content of total riboflavin and its coenzymes (FAD and FMN) in the brain homogenates of rats of different ages by means of fluorimetric ion exchange chromatography was determined. The experiment included 3 age groups of rats: 3 months, 10-12 months, and the old 22-24 months. The dependence of the content of riboflavin and its coenzymes in the cortex, brain stem, cerebellum and large hemispheres from the age of experimental rats was established. The decrease in the content of riboflavin coenzymes in the brain of adult rats and their partial increase in the elderly rats confirms the presence of riboflavin hypovitaminosis, mitochondrial dysmutation and free radical oxidation in the process of aging, and also facilitates the mobilization of adaptive mechanisms aimed at increasing the life span and preserving adaptation to the environment in old animals.